Clinical Laboratorial Perspective on Screening of Prediabetes and need for Standardization of Post Prandial Blood Glucose Testing in Nepal - Pant, Vivek; Pradhan, Santosh; Gautam, Keyoor (Journal of Diabetes and Endocrinology Association of Nepal, 2021)
This study explores the differences in categorization of prediabetes based on fasting blood glucose by the World Health Organization and the American Diabetes Association from a laboratory perspective and the associated implications. As the diagnostic thresholds for prediabetes are based on the likelihood of developing overt diabetes, the criteria for this collective representation of dysglycemic states, including Impaired Fasting Glucose and Impaired Glucose Tolerance needs to be clearly established in the face of a society that grows increasingly concerned about diabetes and its associated complications over time. The authors intend to delve into different published points of view and recommend a categorization in Nepal’s context.